The Effect of Job Satisfaction on Staff Retention and Attrition at GCB Bank PLC in Upper East Region of Ghana - Veronica Muda; Oscar Agyemang Opoku; Jerry Anim; Isaac Opoku-Dadzie (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
The research aimed to assess the link among bank employees using the GCB Bank for the study of job satisfaction and employee attrition. The study employed case study of the quantitative approach. Out of the 325, simple random sampling was adopted to select 130 employees of GCB in Upper East. Questionnaire was the main data collection instrument used. The data gathered were analysed using frequencies, percentages means, and standard deviations as well Pearson correlation and regression. The study found that job satisfaction affects retention of employees. When any component of job satisfaction is troubled, it will directly affect the employee turnover. Employee satisfaction can positively impact the organization as it increases employee productivity, performance, quality of work, profits, commitment to the organization and reduces turnover and absenteeism. Therefore, the study recommended that employers engage in practices that support good working relationships and benefits; job satisfaction improves because workers tend to believe that the company is using their skills, appreciating their service and commitment. In turn, higher job satisfaction generally results in higher levels of employee retention. Also, management should always provide an enabling environment that protects the health and safety of employees and minimizes stress. Incorporate a climate of trust by being honest with employees, treating them fairly, justly and consistently, keeping its words, and showing willingness to listen to the comments and suggestions made by employees during processes of consultation and participation.